Focal epithelial hyperplasia (Heck’s disease): report of a case in a girl of Brazilian Indian descent - W. D. MARTINS, A. A. S. DE LIMA & S. VIEIRA (IAPD and Blackwell, 2006)
The first reports of intraoral epithelial eruptions were made in 1894, and described lesions in Eskimos from Greenland [1].